2010
DOI: 10.1074/jbc.m110.128033
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Human T Cells Alters Their Repertoire of G Protein α-Subunits

Abstract: Because T cell differentiation leads to an expanded repertoire of chemokine receptors, a subgroup of G protein-coupled receptors, we hypothesized that the repertoire of G proteins might be altered in parallel. We analyzed the abundance of mRNA and/or protein of six G protein ␣-subunits in human CD4؉ and CD8

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 82 publications
1
11
0
Order By: Relevance
“…In extreme cases, some G proteins might be present at negligible amounts, even if they couple with the highest efficiency to a particular GPCR. In addition, the repertoire of Gα subunits may also vary throughout development, which could contribute to changes in the nature of the responses to stimulation of a GPCR (74, 75). Third, a host of differentially abundant intracellular factors, such as RGS, AGS, and Ric8 proteins, can further shape GPCR fingerprints.…”
Section: Discussionmentioning
confidence: 99%
“…In extreme cases, some G proteins might be present at negligible amounts, even if they couple with the highest efficiency to a particular GPCR. In addition, the repertoire of Gα subunits may also vary throughout development, which could contribute to changes in the nature of the responses to stimulation of a GPCR (74, 75). Third, a host of differentially abundant intracellular factors, such as RGS, AGS, and Ric8 proteins, can further shape GPCR fingerprints.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our results showed that three (miR‐20a‐5p, miR‐320a and miR‐324‐3p) of the eight plasma markers could be used for the early detection of HCC. As a target of miR‐320a/c/d in HCC cells, GNAI1 participates in numerous physiological processes, such as proliferation, adhesion and differentiation . GNAI1 , which is a member of the Gα inhibitory family, is significantly downregulated in HCC and can inhibit the invasion of HCC cells and play roles in the cyclin D1 pathway and regulation of proliferation .…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, our findings suggest that the CXCR6 structure may have been optimized to perform in a range of cell types by maintaining promiscuous use of G i/o proteins. It is worth noting in this regard that we have shown that even within closely related leukocyte populations, such as subsets of human T cells, there are significant differences in the G i/o protein repertoire (Foley et al, 2010). Our current data show that subtle changes made in CXCR6 to match canonical sequences in the H3C can lead to cell-type specific deficiencies in the use of specific G i/o proteins, which can in turn compromise receptor function.…”
mentioning
confidence: 83%
“…In trying to understand the cell type-specific differences in the behaviors of the various mutants, we considered whether these could be due to differences in the mutants' abilities to couple to particular species of G proteins together with differences in the abundances of G protein species between the cell lines. To make direct quantitative comparisons among the different G protein a-subunit mRNAs by RT-PCR, we established that the corresponding sets of primers and probes showed equal efficiencies of amplification using plasmids containing each of the Ga cDNA sequences as substrates (Foley et al, 2010). We compared the levels of mRNAs for multiple Ga subunits in HEK-293T cells versus Jurkat E6-1 cells (Supplemental Fig.…”
Section: Roles For Noncanonical Sequences In Cxcr6mentioning
confidence: 99%
See 1 more Smart Citation